Waste crankcase oil: An environmental contaminant with potential to modulate estrogenic responses - Ssempebwa, JC; Carpenter, DO; Yilmaz, B; DeCaprio, AP; O'Hehir, DJ; Arcaro, KF (Taylor & Francis Inc, 2004)
Used engine, or crankcase, oil is frequently discarded into the environment resulting in significant pollution of both aquatic and terrestrial ecosystems. The chemical composition of crankcase oils changes with use, and in general, used, or waste, crankcase oil is considered more toxic than the original oil. Polycyclic aromatic hydrocarbons (PAHs) are major constituents of crankcase oil and may exhibit both estrogenic and antiestrogenic activity. In the present study, the estrogenic activity and antiestrogenic activity of both new (unused) and waste crankcase oils were examined in a human breast cancer cell culture assay. Concentrations of 5, 10, 15, 20, or 25 ppm of new oil or waste oil did not alter either the preconfluent or postconfluent cell growth when tested in control medium. in contrast, waste crankcase oil significantly reduced the postconfluent growth of cells grown in medium containing 0.1 nM 17beta-estradiol. Results from mechanistic assays using [H-3]-17 beta-estradiol demonstrated that waste crankcase oil both increased the metabolism of 17 beta-estradiol, and displaced 17 beta-estradiol from the estrogen receptor in MCF-7 cells. The observed antiestrogenic activity of the waste crankcase oil suggests that this pollutant has the potential to alter estrogenic responses, and therefore its presence in the environment may be of concern for reproductive health.
Keywords: Polycyclic Aromatic-Hydrocarbons; Petroleum-Hydrocarbons; Accumulation; Antiestrogenicity; Abnormalities; Activation; Runoff; Health; Crude